Social Workers Response to Domestic Violence and Abuse during the COVID-19 Pandemic. (23rd June 2022) - Holt, Stephanie; Elliffe, Ruth; Gregory, Soma; Curry, Philip
Abstract: The rapid global spread of COVID-19 has put increased pressure on health and social service providers, including social workers who continued front line practice throughout the pandemic, engaging with some of the most vulnerable in society often experiencing multiple adversities alongside domestic violence and abuse (DVA). Movement restrictions and stay-at-home orders introduced to slow the spread of the virus, paradoxically leave these families at even greater risk from those within the home. Utilising a survey methodology combining both open- and closed-ended questions, this study captured a picture of social work practice in Ireland with families experiencing DVA during the early waves of the COVID-19 pandemic. Findings highlight both the changes and challenges in work practices and procedures that limit social work assessment and quality contact with families, changes to the help-seeking behaviours from victims/survivors, as well as emerging innovative practice responses with enhanced use of technology. Implications for practice include an increased awareness of the risk and prevalence of DVA accelerated by the pandemic. Conclusions assert that social work assessment and intervention with families experiencing DVA must remain adaptive to the changing COVID-19 context and continue to develop innovative practice approaches. Abstract : Ireland's COVID-19 restrictions were longer and stricter than in many other European Union countries; a survey was administered to social workers practicing in Ireland to explore their experience of working with DVA during the initial phase of lockdowns; levels of DVA on social work caseloads were estimated to have increased; there were heightened concerns for children in DVA homes who were effectively cut off from safe spaces and protective interactions once the pandemic commenced; as in other jurisdictions, social workers in Ireland demonstrated creative practice solutions to engage with families living with DVA; the study highlights barriers and challenges to social work practice for the initial phase of the COVID-19 pandemic in Ireland; ICT compensated for lack of face-to-face meetings and home visits; and this study has highlighted the importance of ICT policy and practice guidelines to maximise its potential going forward.